Engineering play with blocks as an informal learning context for executive function and planning. Issue 4 (3rd September 2021) - Gold, Zachary S.; Elicker, James; Evich, Carly D.; Mishra, Aura A.; Howe, Nina; Weil, Abigail E.
Abstract: Background: Engineering play is an emerging framework for understanding young children's constructive block play as an engineering design process. Few studies have evaluated engineering thinking, language, or behavior in preschool‐age children, especially quantitative evaluations that systematically document specific early engineering behavior. More research is needed to support diverse children's engineering education in ecologically valid classroom contexts and understand relations with the key cognitive domains that predict school readiness. Purpose/Hypothesis: The present study investigated the associations of executive functioning and planning skills with preschoolers' engineering play behaviors with wooden unit blocks, tested the moderating role of disability status in these associations, and provided additional reliability and validity data on the Preschool Engineering Play Behaviors (P‐EPB) measure. Design/Method: Participants were 110 preschoolers (44% female; 25% children with disabilities) observed and coded during 15‐min block play sessions with a peer partner. Children completed separate formal assessments of executive function and planning. Results: A one‐factor engineering play variable including six behavior categories (i.e., communicating goals, problem‐solving, explaining how things are built/work, following patterns and prototypes, logical and mathematical words, and technical vocabulary) was significantly and positively associated with executive function and planning for children with disabilities. Conclusions: Results provide new knowledge about early engineering measurement and implications for teaching and learning engineering across multiple academic disciplines and with children from diverse developmental backgrounds.